The determinants of competitiveness based on porter's diamond model: The case of paddy farming in Kelantan - Yaacob @ Othman, Azmahani; A Malek @ Abdul Malek, Syazwani; Yusop, Zulkornain (2017)
This study used the Porter’s Diamond Model as the theoretical underpinning to examine the competitiveness of paddy farming in Kelantan.Two (2) different models were used.Model 1 examined only four (4) external factors that were factor conditions, demand conditions, farmers’ strategies and supporting industries while Model 2 include both external and internal factor.The internal factors were chances and government’s roles. Survey questions from prior studies were adopted and customized to collect data.A total of 302 farmers responded to the survey.Partial least Square (PLS) SmartPLS M2 Version 3.0 was used for data analysis.In Model 1, demand conditions was not a factor for the competitiveness but in Model 2, all external factors were significant.Only government’s role (external factor) was not significant. Even these five (5) factors were significant but farmers’ strategies found to be negatively related which is not consistent with the theory.